2016
DOI: 10.1186/s40658-016-0163-2
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular function assessment using 123I/99mTc dual-isotope acquisition with two semi-conductor cadmium–zinc–telluride (CZT) cameras: a gated cardiac phantom study

Abstract: BackgroundThe impact of increased energy resolution of cadmium–zinc–telluride (CZT) cameras on the assessment of left ventricular function under dual-isotope conditions (99mTc and 123I) remains unknown.The Amsterdam-gated dynamic cardiac phantom (AGATE, Vanderwilt techniques, Boxtel, The Netherlands) was successively filled with a solution of 123I alone, 99mTc alone, and a mixture of 123I and 99mTc. A total of 12 datasets was acquired with each commercially available CZT camera (DNM 530c, GE Healthcare and DSP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…As previously reported (22), the presence of 123 I did not have an impact on LVEF assessment within the 99m Tc energy window in the dual-isotope condition for DNM-530c. Accordingly, the LVEF was assessed using Quantitative Gated SPECT software (Cedars-Sinai Medical Center).…”
Section: Hmr Correction Factorsupporting
confidence: 77%
See 1 more Smart Citation
“…As previously reported (22), the presence of 123 I did not have an impact on LVEF assessment within the 99m Tc energy window in the dual-isotope condition for DNM-530c. Accordingly, the LVEF was assessed using Quantitative Gated SPECT software (Cedars-Sinai Medical Center).…”
Section: Hmr Correction Factorsupporting
confidence: 77%
“…Previous studies using phantom data acquired separately for 99m Tc and 123 I showed that 99m Tc cross-talk into the 123 I window was negligible when a simultaneous CZT SPECT acquisition was performed (21,22). To ensure that different 99m Tc/ 123 I ratios did not have an impact on energy resolution, we acquired a set of energy spectra (single 123 I, single 99m Tc, and dual 123 I/ 99m Tc) using linear sources with three 99m Tc/ 123 I ratios (0.5:1, 1:1, and 5:1) and a constant activity of 123 I (24 MBq) ( Fig.…”
Section: Conventional Anger Camera Protocol (Planar Imaging)mentioning
confidence: 99%
“…Furthermore, the greater energy resolution of the CZT camera may allow simultaneous dual isotope imaging of 99m Tc-based and 201 Tl perfusion tracers 53 or molecular imaging agents, such as 123 I-b-methyl-iodophenyl-pentadecanoic acid (BMIPP). 54 It is important to remember that the same energy windows used in performing patient studies should be used for routine, daily QC. Some of the scanners acquire dual energy windows (120 keV for 99m Tc) to allow for scatter correction.…”
Section: Energy Windowsmentioning
confidence: 99%
“…RM correction had an impact on qualitative and Annals of Nuclear Cardiology Vol. showed that global and segmental LV function assessment was also feasible using 99m Tc/ 123 I dual-isotope acquisitions (9). A dynamic cardiac phantom was imaged using two commercially available CZT cameras (DNM 530c, GE Healthcare, and D-SPECT, Spectrum Dynamics) and scatter, cross-talk, and tailing effect corrections were applied when available.…”
Section: Respiratory Motion Correction In Mpimentioning
confidence: 99%